2009
DOI: 10.1111/j.1365-2036.2009.04094.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum HCV RNA levels and HCV genotype do not affect insulin resistance in nondiabetic patients with chronic hepatitis C: a multicentre study

Abstract: SUMMARY BackgroundChronic hepatitis C (CHC) induces insulin resistance (IR) and subsequently diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…In addition, similar to other HCV studies, increasing age, higher BMI, lower HDL levels, and the presence of metabolic syndrome were positively associated with IR. (9, 27) Interestingly, although generally there is a higher prevalence of diabetes among males(30), in this study, female gender was associated with higher IR. It is possible that varying muscle mass and levels of physical activity may account for these gender differences, though these were not assessed.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In addition, similar to other HCV studies, increasing age, higher BMI, lower HDL levels, and the presence of metabolic syndrome were positively associated with IR. (9, 27) Interestingly, although generally there is a higher prevalence of diabetes among males(30), in this study, female gender was associated with higher IR. It is possible that varying muscle mass and levels of physical activity may account for these gender differences, though these were not assessed.…”
Section: Discussioncontrasting
confidence: 45%
“…(9, 27) The viral factors examined here, including HCV duration of infection, viral load, and genotype, did not appear to have much impact on IR, with small estimates that were in the biologically implausible direction. Evidence against any substantial impact, however, was not strong for genotype 1, because the confidence interval extended to a potentially important 19-point increase.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, we observed an association between serum hepcidin and IR. IR is a viral effect of CHC, developing in early stages, and is further exacerbated by metabolic abnormalities [30,31]. In our cohort of mildly overweight patients, a dual viral and metabolic cause of IR is very likely.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HOMA-IR levels are higher in patients with genotypes 1 and 4 [19], and that patients with genotype 3 are those in whom HOMA-IR levels are the lowest [17]. In a study from Greece, HOMA-IR levels were comparable across viral genotypes [124], and these results suggest that the severe steatosis observed in genotype 3 may not result in increased IR. It is noteworthy that SREBP-1c not only influences production of enzymes regulating lipogenesis and reducing fatty acid β-oxidation, but is a protein interfering in intracellular insulin signaling.…”
Section: Relationship Between Insulin Resistance and Steatosis In Hcvmentioning
confidence: 99%